Challenges of patient handover process in healthcare services: A systematic review - Raeisi, Ahmadreza (J Educ Health Promot, 2019)
BACKGROUND: The patient handover process is in fact a valuable and essential part of the care processes in the hospitals. This can be a factor in increasing the quality and effectiveness of medical care. Incorrect and incomplete handover can increase the percentage of errors and cause serious problems for patients. The aim of this study was to identify the handover challenges concerning safety and quality of health services. MATERIALS AND METHODS: A systematic review was conducted according to the Preferred Reporting Item for Systematic Reviews and Meta-analyses guideline. The key words “challenges of patient handover” or “challenges of patient handoff” were used in combination with the Boolean operators OR and AND. The ProQuest, Ovid, Doaj, Magiran, SID, Scopus, Science Direct, PubMed, and ISI were searched. RESULTS: A total of 263 articles were extracted, and 20 articles were selected for final review. The results of selected articles indicated that there are various challenges such as communication, noncoordination, nonuse of checklist, poor management, time management, and other things. These studies reported that communication was the main challenge of handover process. CONCLUSIONS: Hospitals try to provide a lot of services to the patients and other customers in a safe and healthy environment. Lack of communication among the incoming and outgoing nurses in handover process is one of the main causes of reduced safety and quality of services and patient dissatisfaction.